Design and test of a magnetic saturation‐type fault current limiter. Issue 16 (18th January 2019) - Qu, Lu; Zeng, Rong; Yu, Zhanqing; Li, Ge
Abstract : Fault current limiter (FCL) is an effective technique for the fault isolation and protection in the direct current (DC) grid. In this study, a magnetic saturation‐type FCL is designed and tested. Firstly, its basic principle is introduced. Compared with the traditional saturable reactor‐type FCL, it has advantages of simple structure, small size, and better economy. Then design procedure of the magnetic saturation‐type FCL is described, which includes selection of the ferromagnetic materials and determination of parameters of the iron core. After that, a set of principle prototype is designed, and the experiment and simulation are carried out to verify the current limiting ability of the magnetic saturation‐type FCL. Results show that the magnetic saturation‐type FCL can effectively limit the fault current from 110 to 40 A. What is more, the new magnetic saturation‐type FCL can be extended from changing the size of a single core and the distributed arrangement for large‐capacity applications.